SRF promotes gastric cancer metastasis through stromal fibroblasts in an SDF1-CXCR4-dependent manner - Qiao, Juanli (Oncotarget, 2016)
It has been suggested that the overexpression of serum response factor (SRF) in cancer cells may promote cancer metastasis. However, the exact pathway by which SRF promotes metastasis has not been clarified. Here we showed that SRF promotes gastric cancer (GC) metastasis through stromal fibroblasts in an SDF1-CXCR4-dependent manner. SRF expression was significantly increased in metastatic GCs compared with the non-metastatic GCs (n=50, p=0.013). Immuno-staining indicated that SRF was primarily expressed in a-smooth muscle actin (αSMA)-expressing periglandular fibroblasts in GCs. The conditioned medium (CM) from CCD18Co fibroblasts stably transfected with the SRF vector (CCD18Co-SRF) significantly enhanced migration of MKN45 gastric cancer cells. In contrast, the CM from CCD18Co fibroblasts, in which SRF was downregulated, inhibited mobility of MKN45 cells. Similar results were observed in cultured BGC823 cells even when they were treated with the NIH3T3-SRF CM. When MKN45 cells and SRF-upregulated or downregulated CCD18Co cells were simultaneously co-injected into the tail veins of NOD-SCID mice, a significant increase or decrease was, respectively, observed in the experimental pulmonary metastasis of cancer cells. Furthermore, SRF overexpression significantly upregulated `SMA and stromal cell derived factor1 (SDF1) expression in these fibroblasts, and an anti-SDF1 antibody or the SDF1 receptor CXCR4-specific inhibitor AMD3100 treatment completely reversed the SRF-enhanced migration of cancer cells. Quantitative RT-PCR demonstrated that the expression level of SRF was positively correlated with that of SDF1 in 92 GC samples (r=0.63, p<0.001). In conclusion, SRF promote GC metastasis by facilitating myofibroblast-cancer cell crosstalk in an SDF1-CXCR4 dependent manner, and maybe a therapeutic target.